Why the Empty Shells Were Not Fired: A Semi-Bibliographical Note - Itzhak Gilboa (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
This note documents Aumann's reason for omitting the "empty shells" argument for the common prior assumption from the final version of "Correlated Equilibrium as an Expression of Bayesian Rationality." It then continues to discuss the argument and concludes that rational entities cannot learn their own identity; if they do not know it a priori, they never will.
Keywords: 330